Designing the UI/UX for a Shoe Repair Application Using the Design Thinking Method - Tombeng, Marchel; Mambu, Joe Yuan (Malikussaleh University, Aceh, Indonesia, 2024)
The process of designing a mobile application requires a user-centered approach that addresses real-world problems through innovation and creativity. This study focuses on applying the Design Thinking method to develop the UI/UX for a shoe repair service application, aimed at enhancing the user experience for both customers and service providers. The Design Thinking process consists of five stages: empathize, define, ideate, prototype, and test. Through these stages, the study identifies key pain points, such as customers’ difficulties in locating service providers and estimating repair times, and service providers’ challenges in managing customer flow and payment methods. Solutions generated include real-time updates on vendor locations, transparent wait times, and multiple payment options. Prototypes were developed and tested to assess usability, with the research highlighting the need for continuous iteration to improve user experience. The usability testing revealed mostly positive results, with an average usability score of 88.8 across scenarios. However, certain areas, particularly screens in scenario 5, showed higher error rates and required further refinement. This study demonstrates the effectiveness of the Design Thinking method in solving complex design challenges, offering innovative solutions tailored to user needs. The Shoe Repair application’s design not only enhances functionality but also addresses specific challenges faced by users, emphasizing the importance of an iterative, user-focused approach in UI/UX design